Imaginarul plurivalent. Șansa dialogului dintre arte - Alice JURCOVEȚ (Eon)
The article aims to illustrate that the boundaries between the arts are extremely subtle, and it is the imaginary that creates the closest connections between the arts. The fantastic carves out one of its meanings as the temporal segment between the acceptance of the uncanny in everyday life or, on the contrary, another meaning, in which one vehemently denies any possibility of witnessing something extraordinary, which can only be explained by logical inferences, mathematical calculations or famous chemical reactions and verified theories.